Modulation of chloride homeostasis by inflammatory mediators in dorsal root ganglion neurons - Möhrlen Frank; Gensch Thomas; Franjic-Würtz Christina; Woitecki Anne; Funk Katharina; Frings Stephan (SAGE Publishing, 2008)
Abstract Background Chloride currents in peripheral nociceptive neurons have been implicated in the generation of afferent nociceptive signals, as Cl- accumulation in sensory endings establishes the driving force for depolarizing, and even excitatory, Cl- currents. The intracellular Cl- concentration can, however, vary considerably between individual DRG neurons. This raises the question, whether the contribution of Cl- currents to signal generation differs between individual afferent neurons, and whether the specific Cl- levels in these neurons are subject to modulation. Based on the hypothesis that modulation of the peripheral Cl- homeostasis is involved in the generation of inflammatory hyperalgesia, we examined the effects of inflammatory mediators on intracellular Cl- concentrations and on the expression levels of Cl- transporters in rat DRG neurons. Results We developed an in vitro assay for testing how inflammatory mediators influence Cl- concentration and the expression of Cl- transporters. Intact DRGs were treated with 100 ng/ml NGF, 1.8 μM ATP, 0.9 μM bradykinin, and 1.4 μM PGE2 for 1-3 hours. Two-photon fluorescence lifetime imaging with the Cl--sensitive dye MQAE revealed an increase of the intracellular Cl- concentration within 2 hours of treatment. This effect coincided with enhanced phosphorylation of the Na+-K+-2Cl- cotransporter NKCC1, suggesting that an increased activity of that transporter caused the early rise of intracellular Cl- levels. Immunohistochemistry of NKCC1 and KCC2, the main neuronal Cl- importer and exporter, respectively, exposed an inverse regulation by the inflammatory mediators. While the NKCC1 immunosignal increased, that of KCC2 declined after 3 hours of treatment. In contrast, the mRNA levels of the two transporters did not change markedly during this time. These data demonstrate a fundamental transition in Cl- homeostasis toward a state of augmented Cl- accumulation, which is induced by a 1-3 hour treatment with inflammatory mediators. Conclusion Our findings indicate that inflammatory mediators impact on Cl- homeostasis in DRG neurons. Inflammatory mediators raise intracellular Cl- levels and, hence, the driving force for depolarizing Cl- efflux. These findings corroborate current concepts for the role of Cl- regulation in the generation of inflammatory hyperalgesia and allodynia. As the intracellular Cl- concentration rises in DRG neurons, afferent signals can be boosted by excitatory Cl- currents in the presynaptic terminals. Moreover, excitatory Cl- currents in peripheral sensory endings may also contribute to the generation or modulation of afferent signals, especially in inflamed tissue.